Maintaining autonomy: Urban degrowth and the commoning of housing. (May 2023) - Savini, Federico
The theory – and practice – of establishing autonomy from the hegemony of growth is central to the imaginary of degrowth. Yet to envisage pathways towards a degrowth society, scholars need to explain how autonomy coalesces into autonomous institutions. This article addresses this institutional challenge of how to secure autonomy in the provision of collective, affordable and decommodified housing in cities. Building on the tradition of autonomist and (post-)workerist thought, it conceptualises this challenge as one of maintenance. It argues that autonomy occurs through its perpetual reproduction, which is made possible by nesting and federating practices among autonomous communities. Nesting and federating practices allow these communities to avoid becoming enclaves and co-optation by market logics. The article illustrates these arguments through reference to the struggles of de Nieuwe Meent, a recent housing commoning project in Amsterdam.